A Multilevel Analysis of Coaches' Paternalistic Leadership on Burnout in Taiwanese Athletes. Issue 2 (April 2019) - Chang, Chia-Ming; Huang, Hsiu-Chin; Huang, Fang-Ming; Hsieh, Huey-Hong
Using multilevel analysis, this study examined a cross-level effect of paternalistic leadership and team cohesion on athletes' burnout. We called 900 athletes from 28 colleges to participate in this survey, with a return rate of 85.2% and found that paternalistic leadership of coaches had a cross level effect across schools on athletes' burnout. Based on these findings, we propose recommendations for coaches and school administrators.